Music, Cage's Silence, and Art: An Interview with Stephen Davies, PhD - Georgi, Grace (Stance: an international undergraduate philosophy journal, 2022)
Stephen Davies taught philosophy at the University of Auckland, Auckland, New Zealand. His research specialty is the philosophy of art. He is a former President of the American Society for Aesthetics. His books include Definitions of Art (Cornell UP, 1991), Musical Meaning and Expression (Cornell UP, 1994), Musical Works and Performances (Clarendon, 2001), Themes in the Philosophy of Music (OUP, 2003), Philosophical Perspectives on Art (OUP, 2007), Musical Understandings and Other Essays on the Philosophy of Music (OUP, 2011), The Artful Species: Aesthetics, Art, and Evolution (OUP, 2012), The Philosophy of Art (Wiley-Blackwell, 2016 second ed.), and Adornment: What Self-decorations Tells Us about Who We Are, (Bloomsbury Academic, 2020).